2020
DOI: 10.1371/journal.pone.0229488
|View full text |Cite
|
Sign up to set email alerts
|

Regional variations in childbirth interventions and their correlations with adverse outcomes, birthplace and care provider: A nationwide explorative study

Abstract: Background Variations in childbirth interventions may indicate inappropriate use. Most variation studies are limited by the lack of adjustments for maternal characteristics and do not investigate variations in adverse outcomes. This study aims to explore regional variations in the Netherlands and their correlations with referral rates, birthplace, interventions, and adverse outcomes, adjusted for maternal characteristics. Methods In this nationwide retrospective cohort study, using a national data register, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 43 publications
1
26
0
Order By: Relevance
“…However, the existence of comparable guidelines between countries has not yet led to equal quality of care [46]. Studies on regional variations in countries with national guidelines also showed large variations between regions making use of the same guidelines [47,48]. This may be explained by differences in adherence to, and interpretation of, international and national guidelines.…”
Section: Implications and Recommendationsmentioning
confidence: 99%
“…However, the existence of comparable guidelines between countries has not yet led to equal quality of care [46]. Studies on regional variations in countries with national guidelines also showed large variations between regions making use of the same guidelines [47,48]. This may be explained by differences in adherence to, and interpretation of, international and national guidelines.…”
Section: Implications and Recommendationsmentioning
confidence: 99%
“…Amniotomy was the strongest independent modifiable risk factor regardless of parity and suggests that attention to indications and timing of amniotomy may be a hitherto unrecognized means of preventing OASI. The use of amniotomy varies between institutions both in Norway and other countries and ranges from 20% to 60% (34,35). However, in our experience the documentation of amniotomy in patient charts during labour is highly variable.…”
Section: Discussionmentioning
confidence: 84%
“… 33 Our study showed that most care providers were aware of the importance of a restrictive episiotomy policy, but practices often diverged from this restrictive perspective, leading to a liberal rather than restrictive episiotomy practice among some care providers. In a study of Seijmonsbergen-Schermers et al 7 on regional variation of episiotomy in the Netherlands, a higher rate of episiotomy was found in regions with lower rates of home births. In regions with lower rates of home births, episiotomy rates in obstetrician-led care were also higher.…”
Section: Discussionmentioning
confidence: 94%
“… 6 Rates varied among 12 regions from 14% to 42% for nulliparous women and from 3% to 13% for multiparous women. 7 The WHO does not recommend routine or liberal use of episiotomy for women undergoing spontaneous vaginal birth. 8 For instrumental births, episiotomy may be beneficial to prevent Obstetric Anal Sphincter Injury (OASI).…”
Section: Introductionmentioning
confidence: 99%